ANALISIS PENGARUH KUALITAS LAYANAN, KETEPATAN WAKTU PENGIRIMAN DAN FASILITAS TERHADAP KEPUASAN PELANGGAN (Studi pada J&T Express Kota Semarang) - Jaya Sakti, Brillyan; Mahfudz, Mahfudz (Faculty of Economics and Business Diponegoro University, 2018)
Costumer satisfaction are closely related to products or services which are sold to costumer. Besides it, costumer satisfaction can used as success measurement of company performance especially on services company because costumer used directly that services.Â Costumer satisfaction on services company, especially logistic servives can be mesasured by few things, for an example service that company give to costumer, time delivery and facility. This research aims to exam that correlate service quality, on-time delivery and facility to J&T Express costumer satisfaction in Semarang.Sample for this research are random person of 100 costumers that had used J&T Express. Sampling Technique use Accidental Sampling, processed by SPSS 23th edition that use Multiple linier analysis.Result of this research show that servive quality, on-time delivery and facility has significant and positive. On-time delivery variable has a biggest effect for costumer saticfaction.